Good visual outcome in a longstanding macular detachment associated with an optic disc pit treated with vitrectomy, laser, and gas tamponade : case report - Aragao, Ricardo Evangelista Marrocos de (2016)
Optic disc pit is a congenital anomaly of the optic nerve frequently associated with macula detachment. It has a poor visual prognosis if left untreated. The treatment of the optic disc remains controversial and includes the use of laser along the edge of the optic nerve, vitrectomy with gas tamponade with or without removal of posterior hyaloid. We report a case of a 19-year-old female with a longstanding macula detachment due to optic disc pit who was treated with vitrectomy with removal of posterior hyaloid, gas tamponade, and laser. Despite longstanding macular detachment the final visual acuity was 20/25.